1992
DOI: 10.1007/bf00006500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the feeding behavior of Crassostrea gigas (Bivalve Molluscs) on biosedimentation of natural particulate matter

Abstract: Some of the particulate matter found in bottom sediment comes from material rejected as pseudofaeces or produces as faeces by Crassostrea gigas . The amount of pseudofaeces rejected is proportional to the amount of seston for total seston values up to 4 .6 mg 1 -' . For this values up to pseudofaeces production, the amount of faeces is mainly limitated by pseudofaeces production and reaches a constant mean value of 8 .9 mg 1 -' g DW -' when seston concentration increases .The proportion of faeces versus pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 25 publications
0
18
0
2
Order By: Relevance
“…This shift in growth rate is not significant during summer, because the effect of increasing temperature, which is much more important, tends to override the influence of shellfish farming zones. The particulate matter filtered by filter feeders can be recycled in underlying sediments after biodeposition (Deslous-Paoli et al 1992) and directly through excretion (Bayne & Scullard 1977). The enrichment of surface waters in the vicinity of shellfish farms with NH 4 + , SRP and Si illustrates this heterotrophic component induced by bivalves in their ecosystem (Prins & Smaal 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This shift in growth rate is not significant during summer, because the effect of increasing temperature, which is much more important, tends to override the influence of shellfish farming zones. The particulate matter filtered by filter feeders can be recycled in underlying sediments after biodeposition (Deslous-Paoli et al 1992) and directly through excretion (Bayne & Scullard 1977). The enrichment of surface waters in the vicinity of shellfish farms with NH 4 + , SRP and Si illustrates this heterotrophic component induced by bivalves in their ecosystem (Prins & Smaal 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Thompson & Bayne 1974, Epifanio & Edwart 1977, Crisp et al 1985, Deslous-Paoli et al 1992. This is partly due to the saturating nature of the FR as discussed above, but is also a consequence of increasing S resulting only in greater pseudofaeces production (see Foster-Smith 1975, Barillé et al 1997).…”
Section: Treatments Of Oysters and Experimental Designmentioning
confidence: 93%
“…However, there is abundant evidence (e.g. Bayne & Hawkins 1990, Deslous-Paoli et al 1992, Iglesias et al 1992, Barillé et al 1997) that there is selection of organic material in preference to inorganic material at the palps. The sorting of organic material is efficient at low S and inefficient or non-existent at high S (e.g.…”
Section: Treatments Of Oysters and Experimental Designmentioning
confidence: 99%
“…Particle uptake and release as pseudo-faeces only slightly alters the particle composition, so that particles remain available to the other components of the ecosystem (Feuillet-Girard et al 1994). The released fraction of consumed energy comprises between 62 and 92% , 1992, Soletchnick et al 1996, of which 50 to 90% are pseudo-faeces (Deslous-Paoli et al 1992, Soletchnik et al 1993). However, these particles can enrich benthic exchanges in comparison to the pelagic ones.…”
Section: Methodological Choicesmentioning
confidence: 99%
“…An inverse analysis computed with this data showed that an inclusion of the pseudo-faeces production obscures most of the other processes. Moreover, suspension feeders use pseudofaeces to enrich the organic fraction of their diet (Deslous-Paoli et al 1992, Iglesias et al 1992, Bayne et al 1993, Barillé et al 1997) and suspension feeding is a 'highly selective' process (Shumway et al 1985, Graf & Rosenberg 1997. For example, Crassostrea gigas feeds selectively upon the microphytobenthic food supply (Cognie et al 2001) and the pearl oyster Pinctada margaritifera selects its prey on both size and taxonomic criteria (Loret et al 2000).…”
Section: Methodological Choicesmentioning
confidence: 99%